Respostas
respondido por:
1
x + x + 1 + x + 1 + 1 = - 57
3x + 3 = - 57
3x = - 57 - 3
3x = - 60
x = - 60/ 3
x = - 20
x = - 20
x + 1 = - 20 + 1 => - 19
x + 1 + 1 = - 20 + 1 + 1 => - 18
R: O maior deles é - 18.
3x + 3 = - 57
3x = - 57 - 3
3x = - 60
x = - 60/ 3
x = - 20
x = - 20
x + 1 = - 20 + 1 => - 19
x + 1 + 1 = - 20 + 1 + 1 => - 18
R: O maior deles é - 18.
Carla14327:
obrigada
respondido por:
1
(x - 1) + x + (x - 2) = -57
3x - 1 -2 = -57
3x - 3 = -57
3x = -57 + 3
3x = -54
x = -57 / 3
x = -18
===
x = -18
x - 1 => -18 - 1 = -19
x - 2 => -18 - 2 = > -20
===
S = (-18, -19, -20)
3x - 1 -2 = -57
3x - 3 = -57
3x = -57 + 3
3x = -54
x = -57 / 3
x = -18
===
x = -18
x - 1 => -18 - 1 = -19
x - 2 => -18 - 2 = > -20
===
S = (-18, -19, -20)
Perguntas similares
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás